SYNTHESIS OF REFINED CARRAGEENAN FROM EUCHEUMA COTTONII WITH VARIATION OF PRECIPITATING SOLVENT (ASEAN Engineering Journal, 2024)
Red seaweed, Euchema cottonii, is a kappa carrageenan source that grows in Indonesia's coastal areas. Carrageenan is one of the polysaccharides composed entirely of D-galactopyranose units. Besides being used in the food industry, carrageenan is also used in the non-food industry, such as in pharmaceutical, cosmetic, printing, and textile formulations. Various studies have been carried out to produce high-quality Carrageenans. However, the extraction process of carrageenan is quite complicated, and relatively energy intensive. The primary step in carrageenan production is extraction, washing, filtration, precipitation, filtering, pressing, drying, and milling. This study aims to optimize the carrageenan extraction process from red seaweed and characterize the physicochemical of the extracted carrageenan. Red seaweed was extracted using 0.6% of KOH, and the ratio between seaweed and KOH solution was 1:20. Extraction temperature was varied at 30oC and 80oC, and several precipitants, i.e., 96% alcohol, isopropyl alcohol, and KCl were used. The results showed that the best carrageenan extraction process was at 80 oC of extraction temperature and using KCl as a precipitating solvent. From these results, the yield, water content, ash content, viscosity, and L value were 21.24%, 12.56%, 22.69%, 310.96 cP, and 97.93, respectively. Based on the Food Agriculture Organization (FAO) standard, the physical properties of carrageenan produced in this study are under the range permitted by this standard. The study of carrageenans by FTIR spectroscopy shows the presence of S=O of sulfate ester; and C-O of 3,6-anhydrogalactose; galactose and D-galactose-4-sulfate and the results indicated that the carrageenan was κ-type.